Fluid overload as a predictor of morbidity and mortality in pediatric patients following congenital heart surgery - Violeta Castañuela-Sánchez; Alfredo Hernández-Suárez; Luis García-Benítez; Luisa Díaz-García; Guadalupe Martínez-Jasso; Alexis Palacios Macedo-Quenot (Permanyer, 2022)
Background: Patients undergoing congenital heart surgery with cardiopulmonary bypass frequently require the administration of intravenous fluids and blood products due to hemodynamic instability. Correctly performed fluid resuscitation can revert the state of tissue hypoperfusion in the different organs. However, excessive fluid administration and acute kidney injury may promote fluid overload (FO) and increase the risk of complications, hospital stay, and mortality. Methods: We conducted a prospective longitudinal study of pediatric patients with congenital heart surgery and cardiopulmonary bypass in the Pediatric Cardiac Intensive Care Unit (PCICU), Instituto Nacional de Pediatría, from July 2018 to December 2019. Fluid overload was quantified every 24 hours during the first 3 days of stay at the PCICU and expressed as a percentage. We recorded PCICU stay, days of mechanical ventilation, and mortality as outcome variables. Results: We included 130 patients. The main factors associated with fluid overload were age < 1 year (p < 0.001), weight < 5 kg (p < 0.001), and longer cardiopulmonary bypass time (p = 0.003). Patients with fluid overload ≥ 5% had higher inotropic score (p < 0.001), higher oxygenation index (p < 0.001), and longer mechanical ventilation time (p < 0.001). Fluid overload ≥ 5% was associated with higher postoperative mortality (odds ratio 89, p = 0.004). Conclusions: Fluid overload can be used as a prognostic factor in the evolution of pediatric patients undergoing congenital heart surgery since it is associated with increased morbidity and mortality.